The influence of cross-cultural adjustment and personal values on expatriates performances in service industries in Malaysia : mediated by psychological outcomes and moderated by social support network - Shajarina Haji Jalaluddin
Working in a culturally different environment in the globalized and diversity world has always been a challenge by the expatriates and are the major factors contributing to expatriate's failure. The choice of right expatriates in terms of personalities, intercultural training, communication, adapting the learning abilities and skills which has been regarded to increase expatriates' performances resulting from the individual's nationality and background in their hosted country i.e. Malaysia particularly in the services industry such as trading, education, services, food and beverages, hospitality and services. The research was conducted due to the rapid increase of expatriates employed under services industry in Malaysia. Further this study focused on expatriates whom must have been on assignment in Malaysia for at least six months and have a moderate proficiency in English to complete the survey. Therefore, this paper aims to identify the gap between cross cultural and personal values over the expatriates' performances and psychological outcome, as we are still lacking of profound empirical studies about antecedents of perceptions on diversity and its relationship on job performances of expatriates in the services industry in Malaysia. The psychological outcome was tested as mediator while the social support network was tested as the moderator on its effectivity in improving the employee's performance by enhancing employee's psychological well-being. This study has adopted stratified sampling method as it has measured split population with a variety of attributes for determining whether population has to be chosen, based on certain criteria i.e., gender, country of origin, age, designation and marital status, which is a true representation of the existing population from 240 expatriates within different region of Asian, Europe, American and Middle East. The data was analyzed using Partial Least Square-Structural Modelling (PLS-SEM) as it was found to be the most suitable statistic tool to measure many variables. The findings revealed that all hypothesis supported for this study, thus exist positive relationship between all variables.